InAs/GaAs quantum dot solar cells with quantum dots in the base region. Issue 5 (1st October 2019) - Chan, Shun; Kim, Dongyoung; Sanchez, Ana M.; Zhang, Yunyan; Tang, Mingchu; Wu, Jiang; Liu, Huiyun
Abstract : In this work, the influence of quantum dot (QD) position on the performance of solar cells was studied. The presence of QDs within the base regions leads to improved open circuit voltage ( V oc ) from 0.73 to 0.90 V. Despite a slight reduction in short‐circuit current ( J sc ) due to carrier collection loss, the enhancement of the V oc of QDSCs with QDs in base region is significant enough to ensure that power conversion efficiencies ( η ) are higher than the reference quantum dot solar cell (QDSC) of which QDs are embedded in the intrinsic region. Moreover, sample with QDs in deep base region achieved the highest η of 9.75%, an increase of 29% with regard to the reference quantum dot solar cell.